PENGARUH LIFE STYLE, LOKASI, DAN WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN (STUDI KASUS PADA COFFEE SHOP GENRE PANGKALAN KERINCI) - Radhiyya, Fhayza Nanda; Fadli, Mashur (Komunitas Manajemen Kompetitif, 2025)
Abstract: This research aims to find out the influence of lifestyle, location, and word of mouth on purchasing decisions of Coffee Shop Genre consumers in Pangkalan Kerinci. Changes in the lifestyle of modern society, coupled with the role of strategic location and the power of word-of-mouth recommendations, make these three variables important in understanding consumer behavior in purchasing decisions. The research method used is quantitative with a survey approach to consumers who have made purchases at Coffee Shop Genre. The sample in this study consisted of 100 respondents who were determined using non-probability sampling by using accidental sampling and using questionnaires as data collection instruments. The analysis results show that lifestyle, location, and word of mouth have a positive and significant effect on consumer purchasing decisions. This research is expected to provide input for business actors in formulating effective marketing strategies to improve purchasing decisions Keywords: Life Style, Location, Word Of Mouth and Purchasing Decision.